PENGARUH PROFITABILITAS, PERMODALAN, RISIKO KREDIT TERHADAP LIKUIDITAS INDUSTRI PERBANKAN DI BURSA EFEK INDONESIA TAHUN 2017-2019 - Melastiani, Ni Wayan Uri Rahayu; Sudirman, I Made Surya Negara (Buletin Studi Ekonomi; VOLUME.27.NO.2.TAHUN.2022, 2022)
This study aims to obtain empirical evidence regarding the effect of profitability, capital, credit risk on the liquidity of the banking industry on the Indonesia Stock Exchange in 2017-2019. The sampling technique in this study uses purposive sampling with the criteria that commercial banks are listed on the Indonesia Stock Exchange for the 2017-2019 period and have positive profitability during the 2017-2019 period. There are 34 commercial banks that meet the criteria to be used as samples in this study. The analytical technique used in this research is multiple linear regression analysis. The results of the analysis and discussion in this study found that profitability has a significant positive effect on liquidity, capital has a significant positive effect on liquidity, and credit risk has a negative effect on liquidity. Good bank liquidity can increase customer confidence in banking and bank operations is very important for a bank to have liquidity. Bank liquidity must be considered because if there is a liquidity failure in an institution it can cause instability in the banking system and economic disruption and the emergence of liquidity.